Analisis Sanksi Tindak Pidana Pembunuhan Berencana Dalam Putusan Nomor:305/PID.B/2024/PN RBI Perspektif Hukum Pidana Islam - Kholik, Muhamad Abdul; Azazy, Yusup; Najmudin, Deden (Kartika: Jurnal Studi Keislaman, 2025)
The phenomenon of increasing cases of premeditated murder in Indonesia raises academic concerns about the effectiveness of criminal sanctions in providing a deterrent effect and fulfilling a sense of justice. This research is motivated by the discrepancy between the purpose of law that emphasizes social justice and the reality of many perpetrators who are not afraid of criminal threats. The main objective of this study is to analyze the sanctions for premeditated murder according to Indonesian positive law (KUHP), Islamic Criminal Law, and examine the legal considerations of the panel of judges in decision No. 305/Pid.B/2024/PN Rbi. The research method used is normative juridical with statutory, conceptual, and analytical approaches, as well as grammatical and systematic analysis techniques on secondary and primary data. This research is based on the theory of absolute, relative, and combined punishment in positive law, as well as the concepts of qishas, diyat, and ta'zir in Islamic Criminal Law. The results showed that the sentence of life imprisonment to the defendant was formally in accordance with the Criminal Code, but did not fully reflect justice in the perspective of Islamic Criminal Law which gives the victim's family the right to determine the form of sanctions. The implication of this research encourages the need for integration of substantive justice values in the national legal system in order to strengthen the legitimacy of severe criminal decisions